Ecological evaluation of microelements in Astrakhan region and the dynamics of microelements in organs and tissues of Soviet Merino sheep - Ahmed, M. A.; Vorobyov, V. I.; Vorobyov, D. V. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
Microelements are important for stabilizing cell structures, but in deficient conditions they can stimulate alternative pathways and cause disease. This study was aimed to presents the monitoring data on the biogeochemical situation of pasture ecosystems in the Astrakhan region, southern Russia. Microelements in the collected samples from the pasture ecosystem, as well as the organs and tissues of Soviet Merino sheep, were determined by atomic absorption method. It was found a low level of microelements in soil, plants and forages of the ecosystem in the Astrakhan region. In addition, it was found a low level of microelements (selenium, iodine, and cobalt) in the organs and tissues of Merino sheep. Hypomicroelementosis in sheep leads to oxidative stress in animals, lower productivity and decrease the immunity of animals, which can be a predisposing for other diseases.